2020
DOI: 10.3390/biom10020294
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties and Oxidative Stability of Fixed Oil from Plum Seeds (Prunus domestica Linn.)

Abstract: Storage of a great amount of plum kernel waste becomes a challenge for food industry. In this work, the plum seed was used as a source of fixed oil that can be an ingredient of commercial products. Soxhlet extraction was carried out using the different solvents, such as n-hexane, n-heptane, ethyl acetate, acetone, or chloroform:methanol mixture (2:1 v/v). The highest yield of oil (about 30%) was obtained using n-heptane and n-hexane, while the lowest yield was obtained using ethyl acetate. The analysis of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 30 publications
5
26
0
Order By: Relevance
“…As described in the literature, plum seeds contain significant amounts of oil, containing various bioactive compounds, such as lipids, proteins, and phenolic compounds [ 42 , 43 , 44 , 45 ]. It has also been determined that among fatty acids, there are oleic, linoleic, stearic, palmitic, and arachidonic [ 46 , 47 , 48 ]. An ideal filler should have a positive effect on the modified (mechanical and functional) properties of the obtained materials.…”
Section: Introductionmentioning
confidence: 99%
“…As described in the literature, plum seeds contain significant amounts of oil, containing various bioactive compounds, such as lipids, proteins, and phenolic compounds [ 42 , 43 , 44 , 45 ]. It has also been determined that among fatty acids, there are oleic, linoleic, stearic, palmitic, and arachidonic [ 46 , 47 , 48 ]. An ideal filler should have a positive effect on the modified (mechanical and functional) properties of the obtained materials.…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble ash consists of a water-soluble part of the total ash used to determine the amount of inorganic material observed in the herbal drugs [ 18 , 19 , 20 ]. A previous physiochemical study of this plant was compared and found to have very satisfactory results, but the previous study was on seeds of the plant, whereas the present study is on fruit [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of the oil enriched with carotenoids before and after encapsulation in Ca-alginate beads was determined using the DPPH assay [ 32 ]. The Ca-alginate beads did not significantly interfere with the determination of antioxidant activity [ 33 ].…”
Section: Methodsmentioning
confidence: 99%